Impact of health insurance for tertiary care on postoperative outcomes and seeking care for symptoms: quasi-experimental evidence from Karnataka, India - Sood, Neeraj (BMJ Open, 2016)
OBJECTIVES: To evaluate the effects of a government insurance programme covering tertiary care for the poor in Karnataka, India—Vajpayee Arogyashree Scheme (VAS)—on treatment seeking and postoperative outcomes. DESIGN: Geographic regression discontinuity. SETTING: 572 villages in Karnataka, India. PARTICIPANTS: 3478 households in 300 villages where VAS was implemented and 3486 households in 272 neighbouring matched villages ineligible for VAS. INTERVENTION: A government insurance programme that provided free tertiary care to households below the poverty line in half of villages in Karnataka from February 2010 to August 2012. MAIN OUTCOME MEASURE: Seeking treatment for symptoms, posthospitalisation well-being, occurrence of infections during hospitalisation and need for rehospitalisation. RESULTS: The prevalence of symptoms was nearly identical for households in VAS-eligible villages compared with households in VAS-ineligible villages. However, households eligible for VAS were 4.96 percentage points (95% CI 1 to 8.9; p=0.014) more likely to seek treatment for their symptoms. The increase in treatment seeking was more pronounced for symptoms of cardiac conditions, the condition most frequently covered by VAS. Respondents from VAS-eligible villages reported greater improvements in well-being after a hospitalisation in all categories assessed and they were statistically significant in 3 of the 6 categories (walking ability, pain and anxiety). Respondents eligible for VAS were 9.4 percentage points less likely to report any infection after their hospitalisation (95% CI −20.2 to 1.4; p=0.087) and 16.5 percentage points less likely to have to be rehospitalised after the initial hospitalisation (95% CI −28.7 to −4.3; p<0.01). CONCLUSIONS: Insurance for tertiary care increased treatment seeking among eligible households. Moreover, insured patients experienced better posthospitalisation outcomes, suggesting better quality of care received. These results suggest that there are several pathways through which tertiary care insurance could improve health, aside from increasing utilisation of the services that the programme directly subsidises.